1984
DOI: 10.1037/0022-3514.46.2.469
|View full text |Cite
|
Sign up to set email alerts
|

You're only as pretty as you feel: Facial expression as a determinant of physical attractiveness.

Abstract: Photos of IS target persons posing happy, neutral, and sad facial expressions were rated for facial attractiveness using paired comparisons and Likert scales. Half the raters were instructed to compensate for the effects of facial expression. Paired comparisons and Likert ratings were highly correlated. Target persons were less attractive when posing sad expressions than when posing neutral or happy expressions, which did not differ. No effect of compensation instructions was found. In addition, independent ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
2
7

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(123 citation statements)
references
References 44 publications
9
105
2
7
Order By: Relevance
“…Since previous research shows that the assessment of overall attractiveness strongly correlates to the assessment of the attractiveness of the face (Mueser et al 1984), we changed facial characteristics of the models. The models (one boy and one girl) used in this study were the same person in both the moderately attractive and less attractive ad, but were depicted as less attractive by changing some facial characteristics using Photoshop.…”
Section: Design and Stimulimentioning
confidence: 99%
“…Since previous research shows that the assessment of overall attractiveness strongly correlates to the assessment of the attractiveness of the face (Mueser et al 1984), we changed facial characteristics of the models. The models (one boy and one girl) used in this study were the same person in both the moderately attractive and less attractive ad, but were depicted as less attractive by changing some facial characteristics using Photoshop.…”
Section: Design and Stimulimentioning
confidence: 99%
“…Neuroimaging studies have demonstrated that this increased attractiveness of happy expressions is based on the reward system (O'Doherty et al, 2003; for a review, Phan, Wager, Taylor, & Liberzon, 2002). In contrast, negative expressions including sadness, anger, or disgust decrease attractiveness (Mueser, Grau, Sussman, & Rosen, 1984). …”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that faces and bodies have separate cues to attractiveness. Other studies have demonstrated that the face has a relatively greater impact than the body in judgments of overall attractiveness (Currie & Little, 2009;Mueser, Grau, Sussman, & Rosen, 1984;Peters et al, 2007), though this has not been replicated in all studies (Alicke, Smith, & Klotz, 1986). Together, these studies indicate that face and body cues have independent effects on overall attractiveness.…”
Section: Introductionmentioning
confidence: 70%
“…Here, we find that preferences for face cues to apparent height match preferences reported in the body height literature. While the relative impact of face cues to height and actual body height on attractiveness are not known, several studies have found that faces have a greater effect on attractiveness judgments than bodies (Currie & Little, 2009;Mueser et al, 1984;Peters et al, 2007). It is therefore likely that face cues to apparent height would impact perceived attractiveness even when actual body height is directly visible.…”
Section: Discussionmentioning
confidence: 99%